Quranic Features of Healing and Treatment: an Indexing of Quranic (Medical Instructions) Verses - Hussein, Abdul Rahman Obeid; Yusof, Adnan Mohamed; Tarmizi, Syed Ahmad; Omar, Syed; Mohd Amin, Mohd Zohdi (European Scientific Journal, ESJ, 2016)
This paper deals with an important issue in religious thought (religion and modern sciences), which was a great challenge to the eternal validity of the text. Quran, as a revealed book, proved its power in term of legal system, and theological and philosophical presence. However, there has been a controversy on this subject. This paper used the descriptive method in presenting this topic. The researchers found that the major works on this issue have been done by Tantawi Jawhari, Maurice Bucalle, and Zaglul al-Najjar. Additionally, this context has a crucial role to play in classifying some verses as miracles of the Quran.